Effects of Frozen Storage and Sample Temperature on Water Compartmentation and Multiexponential Transverse Relaxation in Cartilage - Reiter, David A. (2011)
Multiexponential transverse relaxation in tissue has been interpreted as a marker of water compartmentation. Articular cartilage has been reported to exhibit such relaxation in several studies, with the relative contributions of tissue heterogeneity and tissue microstructure remaining unspecified. In bovine nasal cartilage (BNC), conflicting data regarding the existence of multiexponential relaxation have been reported. Imaging and analysis artifacts as well as rapid chemical exchange between tissue compartments have been identified as potential causes for this discrepancy. Here, we find that disruption of cartilage microstructure by freeze-thawing can greatly alter the character of transverse relaxation in this tissue. We conclude that fresh cartilage exhibits multiexponential relaxation based upon its microstructural water compartments, but that multiexponentiality can be lost or rendered undetectable by freeze-thawing. In addition, we find that increasing chemical exchange by raising sample temperature from 4°C to 37°C does not substantially limit the ability to detect multiexponential relaxation.